Using Kern's 6-Step Approach to Integrate Health Systems Science Curricula Into Medical Education - Singh, Mamta K; Gullett, Heidi L; Thomas, Patricia A (Academic medicine, 2021)
The term "health systems science" (HSS) has recently emerged as a unifying label for competencies in health care delivery and in population and community health. Despite strong evidence that HSS competencies are needed in the current and future health care workforce, heretofore the integration of HSS into medical education has been slow or fragmented-due, in part, to a lack of evidence that these curricula improve education or population outcomes. The recent COVID-19 pandemic and the national reckoning with racial inequities in the United States further highlight the time-sensitive imperative to integrate HSS content across the medical education continuum. While acknowledging challenges, the authors highlight the unique opportunities inherent in an HSS curriculum and present an elaborated curricular framework for incorporating health care delivery and population health into undergraduate medical education. This framework includes competencies previously left out of medical education, increases the scope of faculty development, and allows for evidence of effectiveness beyond traditional learner-centric metrics. The authors apply a widely adopted 6-step approach to curriculum development to address the unique challenges of incorporating HSS. Two examples-of a module on quality improvement (health care delivery) and of an introductory course on health equity (population and community health)-illustrate how the 6-step approach can be used to build HSS curricula. The Supplemental Digital Appendix (at http://links.lww.com/ACADMED/B106) outlines this approach and provides specific examples and resources. Adapting these resources within local environments to build HSS curricula will allow medical educators to ensure future graduates have the expertise and commitment necessary to effect health systems change and to advocate for their communities, while also building the much-needed evidence for such curricula.